Student and Faculty Outcomes of Undergraduate Science Research Projects by Geographically Dispersed Students - Shaw, Lawton; Kennepohl, Dietmar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Senior undergraduate research projects are important components of most undergraduate science degrees. The delivery of such projects in a distance education format is challenging. Athabasca University (AU) science project courses allow distance education students to complete research project courses by working with research supervisors in their local area, coordinated at a distance by AU faculty. This paper presents demographics and course performance for 155 students over five years. Pass rates were similar to other distance education courses. Research students were surveyed by questionnaire, and external supervisors and AU faculty were interviewed, to examine the outcomes of these project courses for each group. Students reported high levels of satisfaction with the course, local supervisors, and faculty coordinators. Students also reported that the experience increased their interest in research, and the probability that they would pursue graduate or additional certification. Local supervisors and faculty affirmed that the purposes of project courses are to introduce the student to research, provide opportunity for students to use their cumulative knowledge, develop cognitive abilities, and independent thinking. The advantages and challenges associated with this course model are discussed.